Variations in Decision Makers' Use of Information Sources: The Impact of Quality and Accessibility of Information - O’Reilly, Charles A. (Academy of Management Journal, 1982)
Variations in the reported frequency of use of four information sources by decision makers was investigated. Although the perceived quality of information available for decision making was related to the rated importance of information sources, reported frequency of use was found to be primarily a function of the rated accessibility of the sources.